INTOLERANCE OF UNCERTAINTY PREDICTS HAPPINESS OF YOUNG ADULTS IN POST COVID-19 PANDEMIC - Sriyanto, Arie Suciyana; Hakim, Lukman Nul (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2024)
There is evidence that intolerance of uncertainty (IU) is associated with difficulty experiencing positive emotions such as happiness. There is a scarcity of research examining the relations between IU and Happiness during and after the covid-19 pandemic. We examined the degree to which IU predicts Happiness of young adults. This research was conducted using data from 555 participants, age 18 to 35 (SD = 3.34, M = 22.96). Data collected using the online questionnaire used will be created using items derived from two measuring instruments or scales that have been adapted by translating the scale items from English into Indonesian. IU was measured using 12 items the Intolerance for Uncertainty Scale (2 dimensions) from Shihata, McEvoy, and Mullan (2018). The Oxford Happiness Questionnaire (5 dimensions, 29 items) was used to measure happiness. As predicted, IU corelates and predicted happiness. The correlation test between dimensions shows that overall happiness has significant positive correlation with both dimension of IU. On the other hand, the total IU score did not correlate significantly with the life satisfaction dimension of happiness.